Systematic review and meta-analysis of training mode, imaging modality and body size influences on the morphology and function of the male athlete's heart. Issue 23 (9th March 2013) - Utomi, Victor; Oxborough, David; Whyte, Greg P; Somauroo, John; Sharma, Sanjay; Shave, Rob; Atkinson, Greg; George, Keith
Abstract : Context: The athlete's heart (AH) remains a popular topic of study. Controversy related to training-specific cardiac adaptation in male athletes, and continuing developments in imaging technology and scaling prompted this systematic review and meta-analysis. Objective: To provide new insight in relation to: 1) cardiac adaptation to divergent training patterns in male athletes, 2) a developing research database using cardiac magnetic resonance (CMR) in athletes; 3) functional data derived from tissue-Doppler analysis as well as right ventricular (RV) and left atrial (LA) measurements in athletes; and 4) an awareness of the impact of body size on cardiac dimensions. Study design: Systematic review and meta-analysis of prospective trials. Data extraction performed by two researchers. Data sources: Pub Med, Medline, Scopus and ISI Web of knowledge scholarly data base. Study selection: Prospective studies were included if they were echocardiographic or CMR trials of elite young male athletes, with clear indication of type of sports and passed a quality criteria checklist. Results: All left ventricular (LV) structural parameters were higher in athletes than in controls. Only LV end-diastolic diameter and volume were higher in endurance athletes than in resistance athletes: 54.8 mm (95% CI 54.1 to 55.6) vs 52.4 mm (95% CI 51.2 to 53.6); p<0.001 and 171 ml (95% CI 157 to 185) vs 131 ml (95% CI 120 to 142); p<0.001, respectively. RV end-diastolic volume, mass and LA diameter were higher in endurance athletes than controls. LV end-diastolic volume was larger when CMR was used rather than echocardiography: 178 ml (95% CI Q7 162 to 194) vs 135 ml (95% CI 128 to 142); p<0.001. Meta-analysis regression models demonstrated positive and significant associations between body surface area (BSA) and LV mass, RV mass and LA diameter. Conclusions: Morphological features of the male AH were noted in both athlete groups. A training-specific pattern of concentric hypertrophy was not discerned in resistance athletes. Both imaging mode and BSA can have a significant impact on the interpretation of AH data.